Degradation of thiosulfate by sulfide-oxidizing enzyme produced by bacteria locally isolated from effective microorganism active solution (EMAS) - Ashaari, Nur Suhanawati; Md. Salleh, Madihah; Md. Illias, Rosli (School of Postgraduate Studies, UTM, 2006)
A potential aerobic sulfur-oxidizing bacterium (SOB) that was believed to be sulfide-oxidizing enzyme producing strain was previously isolated from Effective Microorganism Active Solution (EMAS), currently known as SO2. This gram negative bacterium was capable of growing autotrophically in sulfur-oxidizer medium, containing 4mM sodium thiosulfate that serves as an energy sources and electron donor. Sulfate ions were the expected end product of sulfide oxidation catalyzed by extracellular sulfide-oxidizing enzyme. The aims of this study are to identify and characterize the SO2 and to induce the activity of sulfide-oxidizing enzyme in this strain. The activity of sulfide-oxidizing enzyme was determined spectrophotometrically by measuring the increase of sulfate production using BaCl2 solution, while the oxidation of thiosulfate was colorimetrically determined at 460 nm. One unit of sulfide-oxidizing activity was defined as amount of enzyme required to produce 1 Âµmol sulfate per min per mL (U). The maximum sulfide-oxidizing activity (0.064 U) was achieved when the strain was grown at pH 5.0, 30ËšC in medium containing 1% (w/v) peptone as nitrogen sources after 15 hours incubation. The specific growth rate of this strain at this condition was 0.1552 h-1, with doubling time value of 4.47 h.